Response of physiological characteristics of ecological restoration plants to substrate cement content under exogenous arbuscular mycorrhizal fungal inoculation - Shu, Qian; Xia, Dong; Ma, Yueyang; Zhang, Yang; Luo, Ting; Ma, Jiaxin; Liu, Fang; Yan, Shuxing; Liu, Daxiang (Frontiers in Plant Science, 2022)
Eco-restoration of vegetation concrete technology has broad application prospects in slope protection and ecological construction. However, the core cementing material of this technology is Portland cement, which can lead to alkaline environment in the substrate, thereby limiting the growth and metabolism of slope vegetation and microorganisms. Arbuscular mycorrhizal fungi (AMF) are ubiquitous reciprocal plant symbionts that promote plant growth and protect them from abiotic stress. Therefore, the introduction of AMF into eco-restoration of vegetation restoration on steep slope can be an effective solution. In this study, Glomus mosseae (GM), Glomus intraradices (GI) and a mixture of two AMF (MI) were used as exogenous inoculation agents and Festuca elata and Cassia glauca were taken as host plants to explore the relation between physiological characteristics of the two plant species and substrate cement content under exogenous inoculation of AMF. The experiment showed that, for festuca elata, the maximum mycorrhizal infection rates of inoculation with GM, MI were with the cement contents ranging 5–8% and the maximum mycorrhizal infection rate of GI was with the cement contents ranging 5 – 10%. Adversely, the mycorrhizal infection of AMF did not have obvious effect on the Cassia glauca with different substrate cement contents. Compared with CK, AMF inoculation could improve(p<0.05) the germination rate, root-shoot ratio (Rs) and the net photosynthetic rate (Pn) of the two plant species. With high cement content, AMF could increase (p< 0.05) stomatal conductivity (Gs) of Cassia glauca, but did not obvious effect on Festuca elata. Moreover, the intercellular co2 concentration (Ci) and transpiration rate (Tr) of single inoculation were higher (p<0.05) than those under mixed inoculation at low cement content levels. The results suggest that the single inoculation of GM should be selected in order to improve the vegetative growth of Festuca elata and Cassia glauca in eco-restoration of vegetation concrete technology.